Role of lncRNAs in Cellular Aging - Degirmenci, Ufuk; Lei, Sun (Frontiers in Endocrinology, 2016)
Aging is a universal, intrinsic and time-dependent biological decay that is linked to intricate cellular processes including cellular senescence, telomere shortening, stem cell exhaustion, mitochondrial dysfunction, and deregulated metabolism. Cellular senescence is accepted as one of the core processes of aging at the organism level. Understanding the molecular mechanism underlying senescence could facilitate the development of potential therapeutics for aging and age-related diseases. Recently, the discovery of long noncoding RNAs (lncRNA) provided insights into a novel regulatory layer that can intervene with cellular senescence. Increasing evidence indicates that targeting lncRNAs may impact on senescence pathways. In this review, we will focus on lncRNAs involved in mechanistic pathways governing cellular senescence.